Immunoglobin G as a novel prognostic biomarker for TNM stages I-III gastric cancer patients - Cheng Xiao-Jing; Lian-Hai Zhang; Xian-Zi Wen (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: Immunoglobin G (IgG) molecules are not only produced by differential B lymphocytes but also expressed in numerous epithelial cancer cells. They play important roles in promoting tumor cell growth and survival. However, their expression and function in gastric cancer remains unkown, this study was designed to investigate IgG expression and function in gastric cancer. Methods: IgG expression was evaluated by immunohistochemistry.The relationship between IgG expression and clinicopathological features and clinical outcomes were statistically analyzed. Results: Statistical analyses showed that IgG expression was more frequently detected in patients with cardiac cancer, intestinal type and no lymph node metastasis. Moreover, IgG expression was significantly related to the overall survivalin patients with tumor TNM stages I-III.Multivariate Cox regression analyses revealed that IgG expression was an independent prognostic factor in patients with tumor TNM stages I-III for OS. Conclusion: Our findings demonstrate that IgG was related to gastric cancer progression, and its expression can serve as a novel prognostic biomarker in gastric cancer patients.